Domestic Violence Act-A Shield Not a Sword: The Hidden Epidemic within Families (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Domestic violenceis extremely complex vicious from of abuse, committed most often within fourwalls of the family or within a particular deep rooted power dynamic andsocio-economic structure, which do not allow even the recognition oracknowledgement of this abuse. A women may of any age, she may girl child,unmarried, married or elderly women including a widow or such women with whommen have marriage like relationship.